PENGARUH INVESTASI, RISK BASED CAPITAL DAN KOMITE AUDIT TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Asuransi yang Terdaftar di Bursa Efek Indonesia) - Agustin Nurhayati; Ratna Ratna; Iswadi Iswadi (J-MIND (Jurnal Manajemen Indonesia), 2022)
This study aims to analyze effect of investment, risk based capital and audit commitee on firm performance in Insurance Companies on Indonesian Stock Exchange during 2010-2020. The number of samples in this study are 9 Insurance Companies which are listed on the IDX and have completed data obtained by porpousive sampling method. The type of data used is secondary data in the form of panel data obtained from the company's Annual Report. The data analysis method used is Panel Data Regression. The results of this study find that investment has a positive and significant effect on firm performance, while risk based capital and audit commite have no significant effect firm performance.